The Use of Fine Arts to Enhance Visualization and Describing Skills in a First-Year Dental Anatomy Course: A Qualitative Study - Geetha Siddanna; Bradley Smith; Andrea Mantesso; Vidya Ramaswamy; Tracy de Peralta; Elisabeta Karl (MDPI AG, 2023)
(1) Background: In this qualitative study, we investigated the implementation of an art-based observation workshop as a tool to improve visualization and interpretation skills in a cohort of first-year dental students (N = 109) in a dental anatomy course. (2) Methods: The art workshop was held once for a total of 60 min in the pre-clinical simulation laboratory, which is the regular teaching setting for the dental anatomy course. Visualization and interpretation skills were assessed before (pre-test) and after the art-based observation workshop (post-test). The pre- and post-tests contained five images that guided students to describe dental anatomy images. The pre- and post-test had different but similar images. Dental students accessed the pre- and post-tests on CANVAS and recorded their answers. After that, the audio recording files were analyzed and compared to determine the frequency of use of dental anatomy-specific nomenclature while answering the pre- and post-test. (3) Results: Our results demonstrate that students used dental anatomy-specific nomenclature more frequently after the intervention. (4) Conclusions: we have concluded that students' use of dental anatomy nomenclature in the first-year dental anatomy curriculum is enhanced following an art-based intervention in a regular dental simulation laboratory.